Transforming trout waste into a liquid fertilizer product to reduce environmental pollution - Bonilla Luis, Deysi Karen (2025)
Globally, the aquaculture industry produces approximately 29 million tons of waste, representing between 60% and 70% of the total [1]. Various studies highlight the importance of organic fertilizer and its growing acceptance in the market; one study reports that 82.2% of respondents expressed interest in purchasing organic products, while the remaining percentage showed a variable disposition towards these products [2]. In the case of trout, the waste generated averages 19% of its live weight. This situation poses a challenge for the efficient management of such waste, as its environmental impact can be detrimental to ecosystems [1], this study focuses on producing liquid fertilizer from trout-generated waste. The primary objective is to analyze the product’s demand to assess its market acceptance. To achieve this, market research was conducted in the Junín region of Peru, including data collection through interviews with companies that commercialize liquid fertilizers and manage aquaculture waste. As a result, it was determined that demand for the project could range between 48,754 and 69,819 liters from 2025 to 2029, indicating high growth potential in the liquid fertilizer market.